Relations between Breastfeeding Self-efficacy and Maternal Health Literacy among Pregnant Women - Elham Charoghchian Khorasani; Nooshin Peyman; Habibollah Esmaily (Mashhad University of Medical Sciences, 2017)
Introduction: Breastfeeding self-efficacy show self-confidence and the ability of mothers to perform breastfeeding and maternal health literacy, ability of women to gain access to, understand, and use information in ways that promote and maintain their health and their children. Aim: this study was Measuring Associations between self-efficacy breastfeeding and maternal health literacy. Methods: This descriptive study was carried out in Mashhad health center in 2015. 185 pregnant women with first experience were selected randomly. Data were collected through health literacy maternal questionnaire and self-efficacy breastfeeding Fox & Dennis questionnaire and analyzed by descriptive and statistical tests in the SPSS/18. Results: The mean score of women's self-efficacy breastfeeding and standard deviation were 120.5 and 11.7 respectively and the mean maternal health literacy was 42.7±5.6. The results regression showed that the only variable that significantly associated with breastfeeding self-efficacy was maternal health literacy. Implications for practice: According to the results of this study, maternal health literacy must be raised to enhance breastfeeding self-efficacy, which could lead to an improvement in maternal breastfeeding in the society.